Feature of Japanese traditional culture - Сaудaнбековa Ш. Т. (Journal of Oriental Studies, 2017)
In this article we’ll give some information about Japanese cultural and traditional values. In order to save national, cultural values and identities of every nation we need to understand that every person should protect and try to save cultural, traditional, spiritual values, keep traditions of their ancestor.